EVALUATION OF FUNCTIONAL CAPACITY IN PATIENTS WITH TOTAL HIP ARTHROPLASTY USING TIME UP GO - TUG INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2026)
Total hip arthroplasty (THA) is widely used to treat degenerative hip joint diseases, promoting pain relief and functional improvement. In this scenario, the Timed Up and Go (TUG) test stands out as a simple, safe, and effective tool for assessing mobility post-THA. This study aimed to analyze the applicability of the TUG in the functional assessment of these patients. Ten studies published between 2010 and 2025 were reviewed. The results indicated that longer TUG times are associated with a higher risk of falls, prolonged hospital stay, and poorer functional recovery, while shorter times indicate earlier discharge and better performance. The test also demonstrated high reliability, even in the early postoperative phase. We conclude that the TUG is a useful clinical tool for monitoring recovery and planning hospital discharge.
Keywords: Total Hip Arthroplasty; Timed Up and Go (TUG); Functional Assessment